2021
DOI: 10.3390/nu13072350
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical Impedance Analysis and Mid-Upper Arm Muscle Circumference Can Be Used to Detect Low Muscle Mass in Clinical Practice

Abstract: Identification of low muscle mass becomes increasingly relevant due to its prognostic value in cancer patients. In clinical practice, mid-upper arm muscle circumference (MAMC) and bioelectrical impedance analysis (BIA) are often used to assess muscle mass. For muscle-mass assessment, computed tomography (CT) is considered as reference standard. We investigated concordance between CT, BIA, and MAMC, diagnostic accuracy of MAMC, and BIA to detect low muscle mass and their relation with the clinical outcome malnu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…BIA has unique advantages in this respect. Studies and systematic literature reviews ( 16 , 17 ) have confirmed that BIA is a useful and reliable tool in the assessment of body composition in children and showed high specificity at detecting low muscle mass in patients. A recent study by Looijaard et al ( 18 ) found that BIA-identified low skeletal muscle mass was consistent with CT scan, a golden standard method.…”
Section: Discussionmentioning
confidence: 93%
“…BIA has unique advantages in this respect. Studies and systematic literature reviews ( 16 , 17 ) have confirmed that BIA is a useful and reliable tool in the assessment of body composition in children and showed high specificity at detecting low muscle mass in patients. A recent study by Looijaard et al ( 18 ) found that BIA-identified low skeletal muscle mass was consistent with CT scan, a golden standard method.…”
Section: Discussionmentioning
confidence: 93%
“…Notably, MUAC measurements are in uenced by the variability of observers' measurement technique and cannot discriminate adipose from non-adipose tissue. BIA showed high speci city at detecting low muscle mass in patients [17]. A recent study by Looijaard et al [18] also showed that BIA and CT identi ed the same critically ill population with low skeletal muscle area on CT scan.…”
Section: Discussionmentioning
confidence: 89%
“…Both the COL11A1 gene and the COL11A2 gene encode one of the two alpha chains of type XI collagen [154]. Mio et al studied the association of the type XI collagen genes, such as COL11A1, COL11A2, and COL2A1, with IVDD, and observed that the COL11A1 gene SNVs, rs1463035 and rs1337185, as well as the COL11A2 gene SNV, rs2076311, were associated with disc bulges [155,156]. While Yang et al observed for the COL11A2 gene that the carriers of the A allele for rs2071025 and carriers of the C allele for rs986522 presented an increased risk of IVDD [157].…”
Section: Osteoporosismentioning
confidence: 99%